Kebijakan Resceduling Dalam Perspektik Hukum Islam - Lely Ana Ferawati Ekaningsih; M. Khozin Kharis; Joharul Fathoni (IAI Darussalam, 2019)
This study aims to determine the policy process of rescheduling as one of the efforts to handle problematic financing and Islamic legal views, especially the Islamic economy towards rescheduling policy as one of the efforts to handle problematic financing in BMT UGT Sidogiri Capem Pesanggaran Banyuwangi district. This type of research is a case study that is testing in detail against one background or one subject or one document storage or a particular event with research data collected both from interviews, observations, and documentation with interactive model analysis. The results of the research show that the policy of distillation is one way to handle problematic financing, where the problem conditions that exist in BMT arise from various aspects, both from the aspects of customers, employees, and nature. Besides that, the rescheduling process at BMT UGT Sidogiri Pesem Pesanggaran is by the procedures and provisions of sharia using the kafalah agreement and Standard Operating Procedure (SOP) that is in the cooperative or non-cooperative.